Characterization of catalyst enzyme by covalent binding chemical immobilization functions on a novel support surface - Mohammed, Weam Abdulwahhab; M-Ridha, Mohanad J. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Cabbage legs peroxidase was used in this study as an economical peroxidase enzyme. Inorganic low-cost supports surfaces such as black stone BS, sand S and quartz rock QR, were utilized to immobilize the catalyst enzyme. One of the chemical processes’ immobilization strategies used was the covalent binding technique. The resulting immobilized enzyme was characterized by SEM, EDS, BET analyses for identification of the main. All supports had their optimal Protein loading, pH, temperature, and reusability evaluated. The results showed that immobilization yield (IY%) was 85, 71, and 60 % for QR, S, BS respectively. The QR support showed an enzyme loading of 12 mg protein / g support, which was the highest capacity, while the S and BS support showed a protein loading of 8 mg protein / g support for each of them. The optimal range for all immobilized biocatalysts was found to be at pH of 6.0. Concerning biocatalyst optimum temperature, the outcome of increased temperature for biocatalyst with QR, S, and BS remains at the same value of 40 °C as the initial optimum temperature of the free enzyme. The biocatalyst enzyme’s immobilization within QR showed great potential for chemical applications and problems associated with engineering.